Digestibility, toxicity and metabolic effects of rapeseed and sunflower protein hydrolysates in mice. Issue 3 (3rd July 2017) - Canistro, Donatella; Vivarelli, Fabio; Ugolini, Luisa; Pinna, Carlo; Grandi, Monica; Antonazzo, Ippazio Cosimo; Cirillo, Silvia; Sapone, Andrea; Cinti, Susanna; Lazzeri, Luca; Conte, Emanuele; Biagi, Giacomo
Abstract: The digestibility ( in vitro ), toxicity and metabolic effects of rapeseed (RPH) and sunflower (SPH) protein hydrolysates have been evaluated in a murine animal model. The enzyme Alcalase ® was employed to obtain a mild enzymatic hydrolysis of rapeseed and sunflower defatted seed meals (DSM) protein isolates. Both hydrolysates showed higher in vitro digestibility than the respective DSM, presumably as a consequence of the hydrolysis process that they had undergone. In vivo, RPH and SPH were well tolerated. Body and organ weights, biochemical blood parameters from treated male mice were comparable to controls. Food intake was regular in RPH and SPH animals, suggesting a good palatability of the hydrolysates. Not relevant perturbations of the principal hepatic and renal drug metabolism enzymes were observed in RPH or SPH mice. In conclusion, protein hydrolysates from sunflower and rapeseed DSM did not determine relevant toxicological effects; therefore, they could be considered as alternative protein sources and/or food ingredients.